Utilization Of Social Media As An Educational Tool Of Political Education On Women’s Politician To Be Learning Organization Development - Anaway Irianti Mansyur, Murti Kusuma Wirasti, M Sukardjo (LLDikti Wilayah IX Sulawesi dan Gorontalo, 2020)
This study aims to identify the use of social media as an educational tool on women politicians to be learning organizations development. The presence of information technology also makes it easy for people who are involved in politics to be able to access information relating to politics with internet including new social media. Political attitudes of society are generally more likely to prioritize conventional political issues rather than hard politics and also have an impact on women. So that learning organizations are needed as a means of political education for women in order to provide freedom for women from inequality in politics. This study uses a qualitative method. Data collection was conducted by interviewed 12 women members of the DPR-RI period 2019-2024, 5 women members of the DPD-RI period 2019-2024, 5 women activists in the political field and 10 women aged 17-20 years who were actively using social media. Documentation is also done to add information through survey. The results showed that social media can be used as a learning organization by women to understand political socialization, and provide opportunities for women to participate in politics. Members of the DPR-RI and DPD-RI can use social media more effectively not only during the election period but after the election period. The use of social media can be used as a tool of political education not only for women but the general public.